Proses Islamisasi Melalui Jalur Perniagaan di Lombok: Sebuah Analisis Historis - Ahsanul Rijal (Kalijaga Journal of Communication, 2019)
In the process of Islamizing the people of Lombok. There are many theories about the entry of Islam in Lombok through commercial channels. As one of the nations with marine wealth, before Islam entered the nation, Indonesia was known as sailors. So, in the process of entering Islam, of course it cannot be separated from marine activities and commerce. This article focuses on commercial activities as the beginning of the entry of Islam in Lombok. By using critical historical and phenomenological approaches from various historical literatures. Based on commerce in observing the process of Islamization and showing the argument that the da’wah process was preceded by economic struggle. This article strengthens the general theory that Islam was brought in by Muslim traders. Also, this article shows that Islam entered by seizing the economic base of the Indonesian people, namely agricultural and maritime commodities. This means that the beginning of Islam did not directly preach religion, but was involved in the economic activities of the people of the archipelago, then Islam was preached. This article is qualitative-descriptive, with local historical databases such as Babad Lombok and Negarakartagama.